Photocontrolled Release of Chemicals from Nano‐ and Microparticle Containers. Issue 9 (16th January 2018) - Englert, Christoph; Nischang, Ivo; Bader, Cornelia; Borchers, Philipp; Alex, Julien; Pröhl, Michael; Hentschel, Martin; Hartlieb, Matthias; Traeger, Anja; Pohnert, Georg; Schubert, Stephanie; Gottschaldt, Michael; et al.
Abstract: A benzoin‐derived diol linker was synthesized and used to generate biocompatible polyesters that can be fully decomposed on demand upon UV irradiation. Extensive structural optimization of the linker unit was performed to enable the defined encapsulation of diverse organic compounds in the polymeric structures and allow for a well‐controllable polymer cleavage process. Selective tracking of the release kinetics of encapsulated model compounds from the polymeric nano‐ and microparticle containers was performed by confocal laser scanning microscopy in a proof‐of‐principle study. The physicochemical properties of the incorporated and released model compounds ranged from fully hydrophilic to fully hydrophobic. The demonstrated biocompatibility of the utilized polyesters and degradation products enables their use in advanced applications, for example, for the smart packaging of UV‐sensitive pharmaceuticals, nutritional components, or even in the area of spatially selective self‐healing processes. Abstract : Chemicals on demand : Biocompatible polyesters were synthesized that can be fully decomposed by UV irradiation. The formation of nano‐ and microparticles allows for the defined encapsulation of structurally diverse organic compounds and a controllable cleavage process. These particles can be used for the smart packaging of UV‐sensitive pharmaceuticals or for spatially selective self‐healing processes.